Phylogeographic evidence for two species of muriqui (genus Brachyteles) - Chaves, Paulo B.; Magnus, Tielli; Jerusalinsky, Leandro; Talebi, Maurício; Strier, Karen B.; Breves, Paula; Tabacow, Fernanda; Teixeira, Rodrigo H. F. [UNESP]; Moreira, Leandro; Hack, Robson O. E.; Milagres, Adriana; Pissinatti, Alcides; et al. (Wiley, 2019)
The taxonomy of muriquis, the largest extant primates in the New World, is controversial. While some specialists argue for a monotypic genus (Brachyteles arachnoides), others favor a two-species classification, splitting northern muriquis (Brachyteles hypoxanthus) from southern muriquis (B. arachnoides). This uncertainty affects how we study the differences between these highly endangered and charismatic primates, as well as the design of more effective conservation programs. To address this issue, between 2003 and 2017 we collected over 230 muriqui fecal samples across the genus’ distribution in the Brazilian Atlantic Forest, extracted DNA from these samples, and sequenced 423 base pairs of the mitochondrial DNA (mtDNA) control region. Phylogenetic and species delimitation analyses of our sequence dataset robustly support two reciprocally monophyletic groups corresponding to northern and southern muriquis separated by an average 12.7% genetic distance. The phylogeographic break between these lineages seems to be associated with the Paraíba do Sul River and coincides with the transition between the north and south Atlantic Forest biogeographic zones. Published divergence estimates from whole mitochondrial genomes and nuclear loci date the split between northern and southern muriquis to the Early Pleistocene (ca. 2.0 mya), and our new mtDNA dataset places the coalescence time for each of these two clades near the last interglacial (ca. 120–80 kya). Our results, together with both phenotypic and ecological differences, support recognizing northern and southern muriquis as sister species that should be managed as distinct evolutionarily significant units. Given that only a few thousand muriquis remain in nature, it is imperative that conservation strategies are tailored to protect both species from extinction.
Keywords: Atelinae; conservation; mtDNA; Platyrrhini; sister species; systematics